Blueberries for Sal - McCloskey, Robert, 1914-2003 (New York : Puffin Books, 1976)
Little Sal and Little Bear both lose their mothers while eating blueberries and almost end up with the other's mother
Keywords: Children -- Conduct of life -- Juvenile fiction; Conduct of life -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Bears -- Juvenile fiction; Blueberries -- Juvenile fiction; Picture books